Optimization, in vitro cytotoxicity and penetration capability of deformable nanovesicles of paclitaxel for dermal chemotherapy in Kaposi sarcoma. (2nd October 2016) - Pathak, Kamla; Sharma, Vijay; Sharma, Meenu
Abstract: Although much research has been published on ways to overcome the low oral bioavailability of paclitaxel, exploration of novel drug delivery systems that can target paclitaxel deep in to the dermal areas in AIDS-related Kaposi sarcoma (KS) have not yet been reported. Our aim was to develop deformable nanovesicles of paclitaxel capable of being used in dermal chemotherapy, especially deep into the dermal areas of AIDS related KS. Deformable nanovesicular formulations (TS1–TS15) composed of soya lecithin and span80 were prepared by the rotary evaporation sonication method within the constraints of our Box–Behnken design. The formulations were subjected to vesicle characterization and ex vivo permeation. The optimized vesicular suspension was formulated as a gel and assessed for in vitro cytotoxicity and penetration characteristics by confocal laser scanning microscopy (CLSM). TS9 with vesicle size characteristics of 185.76 ± 2.15 nm, zeta potential of −23.2 mV, deformability index = 138.02 and cumulative drug permeation of 89.80 ± 1.84% was identified as the optimized formulation. TEM revealed spherical vesicles with firm boundaries that were stable at 4 °C. TS9 was developed as carbopol 934P gel (TG) and compared with the control gel (CG) made with the pure drug (paclitaxel). TG showed significantly higher ( p  < 0.05) in vitro drug permeation and flux compared to the CG. In vitro cytotoxicity study on KSY-1 cell lines revealed higher IC50 (≤17) for TS against IC50 ≤19 for TG. CLSM confirmed the penetrating potential of transfersomes via TG to the dermal layers of skin, the proposed target site. Conclusively, deformable nonovesicles of paclitaxel appear as a feasible alternative to the conventional formulations of paclitaxel in the management of AIDS-related KS.